Pull-out performance of T-stub end plate connected to concrete filled thin-walled steel tube (CFTST) using lindapter hollo-bolts / Nazrul Azmi Ahmad Zamri … [et al.] - Ahmad Zamri, Nazrul Azmi; Petrus, Clotilda; Ibrahim, Azmi; Ab Hamid, Hanizah (Research Management Institute (RMI), 2018)
The application of concrete filled steel tubes (CFSTs) as composite members has widely been used around the world and is becoming popular day by day for structural application especially in earthquake regions. This paper indicates that an experimental study was conducted to comprehend the behaviour of T-stub end plates connected to concrete filled thin-walled steel tube (CFTST) with different types of bolts and are subjected to pullout load. The bolts used are normal type bolt M20 grade 8.8 and Lindapter Hollo-bolt HB16 and HB20. A series of 10 mm thick T-stub end plates were fastened to 2 mm CFTST of 200 mm x 200 mm in cross-section. All of the specimens were subjected to monotonic pull-out load until failure. Based on test results, the Lidapter Hollo-bolts showed better performance compare to normal bolts. The highest ultimate limit load for T-stub end plate fasten with Lindapter Hollo-bolt is four times higher than with normal bolt although all end plates show similar behaviour and failure mode patterns. It can be concluded that T-stub end plate with Lindapter Hollo-bolt shows a better performance in the service limit and ultimate limit states according to the regulations in the design codes.